2020
DOI: 10.4049/jimmunol.1900734
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Coinfection Is Associated with Increased Vascular-Homing CD57+ CD4 T Cells in HIV Infection

Abstract: Cytotoxic CD4 T cells are linked to cardiovascular morbidities and accumulate in both HIV and CMV infections, both of which are associated with increased risk of cardiovascular disease (CVD). In this study, we identify CMV coinfection as a major driver of the cytotoxic phenotype, characterized by elevated CD57 expression and reduced CD28 expression, in circulating CD4 T cells from people living with HIV infection, and investigate potential mechanisms linking this cell population to CVD. We find that human CD57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 78 publications
(80 reference statements)
6
23
0
Order By: Relevance
“…Our data suggest a central role for TNF in endothelial dysfunction and vascular disease. This is consistent with the literature-TNF is upregulated in atherosclerosis [50,51], is a major activator of endothelial cells in vitro [15,33,[52][53][54], and a recent meta-analysis has found that pharmacological targeting of TNF appears to be associated with reduced cardiovascular events in patients with rheumatoid arthritis [55,56]. In addition, plasma levels of soluble TNF receptor (sTNFR)-I and sTNFR-II, which are in vivo markers of TNF activity, highly predict the development of cardiovascular morbidities in PLWH [57].…”
Section: Plos Pathogenssupporting
confidence: 92%
See 3 more Smart Citations
“…Our data suggest a central role for TNF in endothelial dysfunction and vascular disease. This is consistent with the literature-TNF is upregulated in atherosclerosis [50,51], is a major activator of endothelial cells in vitro [15,33,[52][53][54], and a recent meta-analysis has found that pharmacological targeting of TNF appears to be associated with reduced cardiovascular events in patients with rheumatoid arthritis [55,56]. In addition, plasma levels of soluble TNF receptor (sTNFR)-I and sTNFR-II, which are in vivo markers of TNF activity, highly predict the development of cardiovascular morbidities in PLWH [57].…”
Section: Plos Pathogenssupporting
confidence: 92%
“…This difference was also seen with plaque and blood effector memory CD8 T cells in the Moscow cohort ( Fig 2I), suggesting that plaque-derived CD57+ CD8 T cells may have been recently exposed to CX3CL1 which we propose targets them to the plaque in vivo. We recently observed similar evidence for activation and CX3CL1 exposure in plaque-infiltrating CD4 T cells [33].…”
Section: Cx3cl1 and Il-15 Expression Is Enriched In Human Atherosclersupporting
confidence: 59%
See 2 more Smart Citations
“…Further, a recent publication using single cells isolated from carotid plaque samples of HIV-negative individuals, showed expression of CX3CL1 in nascent plaque and CX3CR1 + CD57 + CD4 + T cells within the plaque by flow cytometry. 27 They did not include plaque from HIV-positive samples which we address in this study.…”
Section: Introductionmentioning
confidence: 99%